2013
DOI: 10.1111/jen.12053
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficacy of a vinegar trap for Drosophila suzikii (Diptera; Drosophilidae)

Abstract: Drosophila suzukii, Matsumura, is a relatively new pest in the United States attacking a variety of fruit crops. Studies were conducted to develop a standardized, economical trap for monitoring. Laboratory bioassays found that flies were attracted to dark colours ranging from red to black. Similarly, fly catches in 237‐ml plastic ‘spice’ jars with ten 0.48‐cm holes and baited with apple cider vinegar were significantly higher in jars with red or black than white caps. The use of an alternating set of three, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 14 publications
3
54
0
Order By: Relevance
“…Caged choice bioassays showed D. suzukii was more likely to be first attracted to black, red, and burgundy cards than to yellow cards (Basoalto et al 2013). However, field studies, including the current one, indicate D. suzukii's preference for red over yellow does not extend to the field.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Caged choice bioassays showed D. suzukii was more likely to be first attracted to black, red, and burgundy cards than to yellow cards (Basoalto et al 2013). However, field studies, including the current one, indicate D. suzukii's preference for red over yellow does not extend to the field.…”
Section: Discussionmentioning
confidence: 68%
“…One element of this research has been whether a color preference exists that can improve the efficiency of early season traps, which are important in establishing economic thresholds. Cage experiments offering choices between cards of 9 colors showed that darker colors attracted D. suzukii more than lighter colors (Basoalto et al 2013). Significantly more flies landed first on red, burgundy, and black cards than white, yellow, and light blue cards.…”
Section: Introductionmentioning
confidence: 98%
“…Undoubtedly, many types of alterations to trap design might be evaluated as possible improvements over the current traps used in this study. For example, a recent study showed the importance of colors and visual patterns on the efÞciency of trapping D. suzukii by using traps baited with ACV (Basoalto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Yellow has been shown to be attractive for many insects including plant-feeding dipterans because it constitutes a foliage-type stimulus (Prokopy and Owens 1983). Recent laboratory studies investigating differences in color preference for spotted wing drosophila showed a higher afÞnity toward darker colors such as red, burgundy, and black compared with lighter colors like white and light blue (Basoalto et al 2013). However, Þeld studies showed that clear traps can be just as effective as red traps of the same design in a number of spotted wing drosophila host fruits .…”
mentioning
confidence: 98%
“…Several types of traps have been tested for spotted wing drosophila including handmade plastic cups with 1 to 10 entry holes (the most commonly recommended), traps with mesh entries, and plastic cups with tents to provide shade and prevent water from entering (Kanzawa 1939, Wu et al 2007. Dome traps and commercial "spice" jar traps have also been evaluated (Landolt et al 2012a, Basoalto et al 2013) with varying degrees of success. Other trap modiÞcations include the addition of a yellow sticky card hanging inside the trap and odorless dish detergent to the drowning solution to help prevent ßy escape (Landolt et al 2012a,b;Lee et al 2012;Van Timmeren and Isaacs 2013).…”
mentioning
confidence: 99%